Systematic Literature Review of Google Sites-Based Digital Teaching Materials for Function Composition in Vocational High Schools - Huda; Amami Pramuditya, Surya (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
The development of digital technology has encouraged the use of web-based learning media to improve students' understanding of mathematical concepts. One of the platforms used is Google Sites, which allows the integration of text, images, videos, and interactive exercises in a single learning medium. This article aims to review the literature related to the use of Google Sites in mathematics learning, specifically Function Composition material at the vocational high school level, and analyze its effectiveness on student learning outcomes through pre-tests and post-tests. The method used is a literature study with descriptive analysis of scientific articles, journals, and related publications published between 2019 and 2025. The results of the study show that Google Sites is effective in improving students' conceptual understanding, engagement, and learning motivation, although research focusing on Function Composition material in vocational high schools is still limited. These findings emphasize the importance of appropriate media design, teacher assistance, and systematic learning outcome evaluation. This article provides a basis for the development of digital teaching materials and further research to improve the quality of mathematics learning in vocational high schools.